Torture and moral integrity : a philosophical enquiry - Kramer, Matthew H., 1959- (Oxford : Oxford University Press, 2014)
The morality of interrogational torture has been the subject of heated debate in recent years. In explaining why torture is morally wrong, Matthew Kramer engages in deep philosophical reflections on the nature of morality and on moral conflicts.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on May 20, 2014).
Keywords: Torture -- Moral and ethical aspects